KUALITAS PELAYANAN TERHADAP PELANGGAN PADA PT. POS INDONESIA (PERSERO) BANDA ACEH - Dedi Sufriadi (Universitas Teuku Umar, 2018)
Facing future shipping competition, the quality of service to customers is an unavoidable demand. The purpose of the author is to find out about the quality of service to customers at PT. Pos Indonesia (Persero) Banda Aceh. In collecting the data needed, the writer uses two ways, namely library study, and field study by conducting direct interviews with the competent parties in charge of service at PT. Pos Indonesia (Persero) Banda Aceh, as well as observations. The results of the study found that service quality standards for customers at PT. Pos Indonesia (Persero) Banda Aceh is speed, ease and comfort. The role of providing high quality services to customers, to cause decisions from customers to immediately provide goods / services offered at that time, to foster customer trust in the goods / services offered, to create customer trust and satisfaction. The service function is to serve customers with a friendly, precise, and fast, and satisfy customers to want to do business again with the company. Types of services at PT. Pos Indonesia (Persero) Banda Aceh is a regular postal letter and express mail, postal money order, postal parcel, checking and postal check service, additional services, special services, agency services. In providing services to the community of PT. Pos Indonesia (Persero) Banda Aceh has a service facility in the form of form, waiting room, table, pens, stamps, envelopes, boxes, tromolpos, postal buses and equipment to wrap packages. The items that are forbidden to be sent using the services of PT. Pos Indonesia (Persero) Banda Aceh is goods that are quickly damaged, explosive items, live animals, plants, drugs, liquid goods, and sharp items. Keywords: quality of service to customers